Anaerobic digestion of dairy manure wastewater, food and fruit waste, a sustainable source of bio-energy and waste management - Sakeus, Kafula (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.